2017
DOI: 10.15406/jnhfe.2017.07.00245
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity during the Gestational Period and Factors Associated with Maternal and Child Health

Abstract: More studies are needed to understand the impact of gestational food insecurity on maternal and child health in order to contribute to the development of health policies that can guarantee the food and nutritional security of the binomial mother and child. AbstractFood security consists in granting everyone's right to regular and permanent access to safe, nutritious and sufficient food to meet their dietary needs and food preferences in order to lead to an active and healthy life. Studies that analyze aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(17 reference statements)
0
7
0
2
Order By: Relevance
“…Despite being indirectly correlated, a low household income increases the likelihood of triggering food insecurity, since money available to buy food competes with other basic needs' expenses such as rent, energy, water, sewage, transportation, among other bills, which sets the scenario for an increased risk of giving birth and raise a child in a food-insecure environment, 18 which in turn interferes with fetal growth and development. 19 The 2018 national survey (PNAD) disclosed that the average national monthly income was R$ 2,222 and in Minas Gerais it was R$ 1,950. The present study showed that the average household monthly income to which the pregnant woman lived with was R$ 1,631.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being indirectly correlated, a low household income increases the likelihood of triggering food insecurity, since money available to buy food competes with other basic needs' expenses such as rent, energy, water, sewage, transportation, among other bills, which sets the scenario for an increased risk of giving birth and raise a child in a food-insecure environment, 18 which in turn interferes with fetal growth and development. 19 The 2018 national survey (PNAD) disclosed that the average national monthly income was R$ 2,222 and in Minas Gerais it was R$ 1,950. The present study showed that the average household monthly income to which the pregnant woman lived with was R$ 1,631.…”
Section: Discussionmentioning
confidence: 99%
“…Em classes socioeconômicas inferiores, a maior probabilidade de insegurança alimentar moderada/grave, entre mães que não receberam suplementação durante a gravidez, segue a tendência mostrada em estudo prévio no qual os cuidados inadequados na gestação, incluído a suplementação com micronutrientes, representou maiores chances de IAN em graus mais severos 27 . Os efeitos da IAN podem ser vistos principalmente entre os grupos mais vulneráveis, nos quais a falta de alimentos saudáveis e de qualidade pode estar relacionada ao acesso precário a renda, bens e serviços 36 . A consistência desses achados também encontra explicações segundo uma revisão da literatura que destaca o nível socioeconômico como o principal determinante da suplementação com ácido fólico na gestação 37 , sendo que a IAN medida por meio da EBIA é considerada um importante indicador de iniquidade social 38 .…”
Section: Discussionunclassified
“…This may be because food insecurity among women during pregnancy ranges up to 90% in underdeveloped and developing countries. 19 Since there is an increased demand for nutrients during pregnancy, 20 pregnant women must have adequate quality and quantity of food. Foodinsecure mothers have limited or uncertain availability of nutritionally adequate food, which prevents them from meeting the guidelines for healthy eating during pregnancy and leads to their infants having LBW.…”
Section: Discussionmentioning
confidence: 99%